UJI KELAYAKAN DESAIN KEMASAN PRODUK MAKANAN OLEH-OLEH UMKM JAWA BARAT MENGGUNAKAN CHI-SQUARE - Hartanti, Monica; Pradita, Puspita Yuli (Institut Bisnis dan Teknologi Indonesia, 2021)
Souvenir products produced by SMEs in the city of Bandung are very diverse. The COVID-19 pandemic has caused the tourism industry to decline; souvenirs cannot be purchased directly at tourist sites. Advances in technology and government support for Micro, Small, and Medium Enterprises (SMEs) have opened up opportunities to migrate to sell products online. The souvenir food products need to be packaged attractively and have local characteristics because local identity can be one of the unique things that will attract consumers. Nine samples of food products as souvenirs from the Sabilulungan Community SMEs, assisted by Department of Industry and Commerce Soreang Regency, West Java, have redesigned their packaging. The old and new packages were arranged side by side; a comparative study was conducted, measured respondents' design tastes, respondents' reasons for choosing designs, and product sales results using the Chi-Square test. The data collection method is by distributing questionnaires filled out when visitors shop at the product bazaar. The results of data calculations reveal that well-designed packaging and have an identity that matches the food will increase purchases. Local characteristics can be used as an identity that is displayed aesthetically and uniquely to increase the value of local products. Local characteristics that are easiest for consumers to remember are symbols of local and familiar colors culture. A Packaging that uses zippers and is not too big is considered more efficient from the usability aspect. The form of packaging that is not just a box is considered more unique.